How to measure the environmental risks from uses of plant protection products for achieving the IPM requirements and risk communication : A case study on the production chain of cereal farming in Finland - Räsänen, Kati; Nousiainen, Riikka; Kurppa, Sirpa; Autio, Sari; Junnila, Sanni; Tiilikkala, Kari; Kaseva, Janne; Laitinen, Pauliina (Maa- ja elintarviketalouden tutkimuskeskus, 2013)
Indicators are needed in the monitoring of risk reduction actions according to the EU strategy, where the aim is to reduce health and environmental risks via integrated pest management (IPM). The actions are based on EU legislation by the directive for sustainable use of plant protection products (PPPs) (2009/128/EC). PPP sales data are examples of present indirect indicators, which do not reflect the actual risks caused by various types of pesticides. In this study, we introduce a novel approach, the procedure, to specifically assess the progress of IPM in reducing environmental risks, and for achieving sustainable development as required. The study was done as part of the PesticideLife project (2010–2013) coordinated by MTT Agrifood Research Finland and co-financed by EU LIFE+ programme. With the procedure the field usage of PPP effects were demonstrated in two dimensions. In the vertical dimension, the demonstration of potential PPP environmental impacts was assessed in terms of the food chain with the ecotoxicity impact of LCA. PestLCI 2.0 was used to estimate the emissions assuming average Finnish field conditions and the SETAC consensus LCIA model for ecotoxic impacts – USEtox™ – was used for characterisation factors. In the horizontal dimension, the demonstration of environmental risks on the landscape were evaluated using the aquatic risk indicators of EU HAIR2010 (HArmonised environmental Indicators for pesticide Risk). The data for the demonstrations was based on PPP usage and sales in Finland. The field scale PPP usage data (kg of active ingredient per hectare) was obtained from a case study carried out by the Finnish Information Centre of the Ministry of Agriculture and Forestry (Tike), covering data from 2007 and crop farms in Finland. Sampling of the case data by Tike was also a pilot study to prepare for collecting pesticide usage data regularly in the future by Finnish authorities. The PPP sales data was obtained from the Finnish Safety and Chemicals Agency (Tukes). Three model crops of spring wheat, feed barley and oats, and four model substances of MCPA, glyphosate, prothioconatzole and α-cypermethrin were used in this work. In performing the vertical impact and horizontal risk demonstrations with the procedure, the three following steps were taken: 1. mapping of the PPP usage, 2. impact and risk assessment calculations at a countrywide scale in Finland, and 3. impact and risk assessment calculations at the regional scale (ELY-centres in Finland). In the future, the results of this procedure, i.e. results obtained from different time periods, would describe impacts of the choices for the farmers working in the frame of IPM. In this study, we suggest to provide the authorities with this procedure for assessing of performance of IPM actions. Additionally, the proposed procedure and results can be used for different risk communication purposes. Further work is necessary for drawing more general conclusions on the patterns of environmental risks and IPM processing induced by the usage of plant protection products in Finland.

Indikatorer behövs för att övervaka åtgärder för riskreduktion i enlighet med EU:s strategi, som går ut på att minska hälso- och miljöriskerna genom integrerat växtskydd (IPM). Åtgärderna bygger på EU-lagstiftningen i direktivet för hållbar användning av bekämpningsmedel (2009/128/EG). Försäljningsdata för bekämpningsmedel är exempel på befintliga indirekta indikatorer, som dock inte återspeglar de faktiska riskerna med olika typer av bekämpningsmedel. I denna studie introducerar vi en ny metod som ger en bättre helhetsbild av IPM-arbetets framsteg, genom att den inkluderar både möjligheten att bedöma utvecklingen inom hållbar användning av bekämpningsmedel samt riskarbetet kring bekämpningsmedel. Studien utfördes inom projektet PesticideLife (2010–2013) som samordnas av Forskningscentralen för jordbruk och livsmedelsekonomi MTT i Finland och samfinansieras av EU-programmet LIFE+. Denna metod gör det möjligt att demonstrera effekterna som orsakats av de bekämpningsmedel som använts i fältstudien i två dimensioner. I den vertikala dimensionen bedömdes bekämpningsmedlens potentiella miljöinverkan på livsmedelskedjan och livscykelanalysens (LCA) ekotoxicitetsinverkan. PestLCI 2.0 användes för att uppskatta utsläppen utifrån genomsnittliga finska odlingsförhållanden, och modellen USEtox™ – SETAC:s LCIA-model för ekotoxisk inverkan – utnyttjades för att få fram karaktäriseringsfaktorer. I den horisontella dimensionen bedömdes miljöriskerna per landskap med akvatiska riskindikatorer från EU HAIR2010 (HArmonised environmental Indicators for pesticide Risk). Uppgifterna byggde på användningen och försäljningen av bekämpningsmedel i Finland. Uppgifterna om bekämpningsmedlens användning på fältet (antal kilo aktiv ingrediens per hektar) erhölls från en fallstudie som utfördes av finska Jord- och skogsbruksministeriets informationstjänstcentral (Tike), och som innehöll uppgifter från 2007 från odlingsjordbruk i Finland. Denna datainsamling som Tike genomförde var en pilotstudie med syftet att myndigheten i framtiden regelbundet ska kunna samla in användningsinformation gällande bekämpningsmedel. Uppgifterna om försäljning av bekämpningsmedel erhölls från finska Säkerhets- och kemikalieverket (Tukes). I studien användes tre modellväxter, vårvete, foderkorn och havre, och fyra bekämpningsmedel: MCPA, glyfosat, protiokonazol och α-cypermetrin. Metodens vertikala och horisontella risker har demonstrerats i tre steg: 1. kartläggning av bekämpningsmedelsanvändningen, 2. bedömning av inverkan och risk på nationell nivå i Finland, 3. bedömning av inverkan och risk på regional nivå (ELY-centraler i Finland). I framtiden kommer resultaten från denna metod som erhållits under olika år att återspegla de val odlarna gjort vad gäller integrerat växtskydd. I studien vill vi även erbjuda myndigheter att använda metoden i fråga. Metoden i fråga samt resultaten den ger kan även användas för olika typer av riskkommunikation. Det krävs ytterligare studier för att kunna dra slutsatser gällande vilka miljörisker bekämpningsmedel orsakar, samt hur arbetet med IPM-metoden fortskrider i Finland.

EU:n terveys- ja ympäristöriskejä vähentämään pyrkivän, integroidun kasvinsuojelustrategian (IPM = integrated pest management) mukaisen toiminnan seuraamiseen tarvitaan indikaattoreita. Toiminnat perustuvat EU:n lainsäädännön direktiivillä (2009/128/EC) tapahtuvaan ohjaukseen, jonka tarkoituksena on kasvinsuojeluaineiden kestävä käyttö. Kasvinsuojeluaineiden myyntitiedot ovat yksi esimerkki indikaattoreista, mutta ne eivät tosiasiassa kuvaa erilaisten aineiden aiheuttamia todellisia riskejä. Tutkimuksessamme esittelemme uuden menettelytavan, jolla voidaan arvioida kasvinsuojeluaineiden kestävän käytön kehittymistä ja kasvinsuojeluaineita koskevan riskinhallinnan tilaa eli kokonaisvaltaisemmin IPM:n edistymistä. Tutkimus on tehty PesticideLife -hankkeessa (2010–2013), jota koordinoi Maa- ja elintarviketalouden tutkimuskeskus MTT ja joka on osittain rahoitettu EU LIFE+-ohjelman kautta. Menettelytavassa peltolohkon kasvinsuojeluaineiden käytöstä aiheutuvia vaikutuksia demonstroidaan kahdessa suunnassa (dimensiossa). Vertikaalisessa demonstraatiossa kasvinsuojeluaineiden ympäristövaikutuksia arvioidaan ruokaketjun suuntaan elinkaariarvioinnin (LCA = life cycle analysis) ekotoksisella ympäristövaikutusluokalla. Tutkimuksessa käytettiin PestLCI 2.0 -mallia arvioimaan Suomen pelto-olosuhteista saatuja keskiarvoisia päästöjä sekä ekotoksisen SETAC LCIA -vaikutusluokan USEtox™ –mallia karakterisointikertoimien laskemisessa. Horisontaalisessa demonstraatiossa ympäristöriskejä arvioitiin alueellisesti EU:n HAIR2010 (HArmonised environmental Indicators for pesticide Risk) akvaattisilla riski-indikaattoreilla. Demonstraatioissa käytetty aineisto perustui kasvinsuojeluaineiden käyttö- ja myyntitietoihin vuodelta 2007. Peltolohkojen kasvinsuojeluaineiden käyttötiedot (kg tehoainetta hehtaaria kohti) saatiin Suomen Maa- ja metsätalousministeriön tietopalvelukeskukselta (Tike). Tike:n tekemä käyttötietojen keruu oli heille samalla pilottitutkimus, jonka tavoitteena jatkossa on kerätä torjunta-aineiden käyttötietoja säännöllisesti Suomen viranomaisena. Kasvinsuojeluaineiden myyntitiedot saatiin Suomen Turvallisuus- ja kemikaalivirastosta (Tukes). Tutkimuksessa käytettiin kolmea mallikasvia (kevätvehnä, rehuohra, kaura) ja neljää ainetta (MCPA, glyfosaatti, protiokonatsoli, α-sypermetriini). Menettelytavan vertikaaliset ja horisontaaliset riskit demonstroitiin kolmella tasolla: 1. kasvinsuojeluaineiden käytön mallintaminen kartalla, 2. vaikutusten ja riskien arviointien laskeminen koko Suomen tasolla, 3. vaikutusten ja riskien arviointien laskeminen aluetasolla (ELY-keskukset Suomessa). Tulevaisuudessa menetelmällä eri vuosilta saadut tulokset tulevat kuvaamaan viljelijöiden tekemiä kasvinsuojeluvalintoja IPM:n toteuttamisessa. Tutkimuksessamme halusimme myös tarjota kyseisen menettelytavan viranomaiskäyttöön IPM -toimien arvioimiseen. Kuvattua menettelytapaa ja sen tuloksia voidaan käyttää erilaisiin riskiviestinnän tarkoituksiin. Lisätutkimusta tarvitaan, jotta voidaan tehdä johtopäätöksiä kasvinsuojeluaineiden aiheuttamista ympäristöriskeistä ja IPM:n edistymisestä Suomessa.
Hur mäter man miljöriskerna vid användning av bekämpningsmedel för att uppnå IPM-kraven och kommunicera riskerna? : – En fallstudie på produktionskedjan vid odlingsjordbruk i Finland
Keywords: Kasvintuotanto, kasvinviljely, maaperä; Ympäristönsuojelu; integrated pest management; IPM; indicator; environmental risks; ecotoxicity; life cycle assessment; PestLCI; USEtox™; HAIR risk indicators; plant protection product; active ingredient; risk communication; integrerat växtskydd; IPM; indikator; miljörisk; ekotoxicitet; livscykelanalys; PestLCI; Usetox; HAIR-riskindikator; växtskyddsmedel; aktiv ingrediens; riskkommunikation; integroitu kasvinsuojelu; IPM; indikaattori; ympäristöriskit; ekotoksisuus; elinkaariarviointi; PestLCI; USEtox™; HAIR-riski-indikaattorit; tehoaine; riskiviestintä; torjunta-aineet